Evaluation of implant stability using different implant drilling sequences - Hyeon Min Kim; Jin-yong Cho; Jaeyoung Ryu (Elsevier, 2019)
Background/purpose: Simplifying the drilling sequence would be meaningful for implant surgery, if it does not exert a negative influence. This prospective clinical study was conducted to evaluate the stability of implant placements after simplifying the drilling sequence. Materials and methods: Subjects were divided into a control group that underwent a normal drilling sequence or a test group that underwent only an initial and final drilling. To evaluate the stability of the placed implant, radiography and implant stability quotient (ISQ) measurements were recorded immediately and 5 months after placement. Results: In all subjects, the prosthesis process was completed with no significant resorption of the marginal bones. In contrast, a statistically significant difference was observed between the control and test groups 5 months after the implants were placed in terms of the ISQ score (80.72 ± 6.76 and 71.83 ± 9.00, respectively); however, both scores were sufficient to proceed with the prosthesis process. Conclusion: These attempts to simplify drilling protocols are expected to contribute the improvement of implant-related treatments in future. Keywords: Dental implant, Drilling protocol, Implant survival